Fetal ascites in Indian buffaloes – Three cases - Patil, Anil Dinkarrao; Razzaque, Waquar Ahmed Abdul; Alai, Rakesh Vasudev (Buffalo Bulletin, 2023)
Fetal ascites was found in three Indian buffaloes. The cases were diagnosed and treated successfully. Abdomen of the fetus was blindly punctured, and fetuses were removed by applying the traction.